A New Role for the European Stability Mechanism in Post-COVID-19 EMU? Explaining the Failure of the Pandemic Crisis Support and Assessing Ways Forward. Issue 1 (2nd January 2022) - De Angelis, Gabriele
Abstract: Since the establishment of the Pandemic Crisis Support, it has been hypothesized that the European Stability Mechanism might play a new role in stabilizing investments in the European Economic and Monetary Union through a targeted support for the financing of European public goods. The article inquires into the changes in the European Stability Mechanism's institutional design that could make this possible. It starts by analyzing its lending policy, its accountability structure, and the structure of incentives that underlie negotiations at the Board of Governors. The article then explains the failure of the Pandemic Crisis Support against the background of a neo-institutionalist analysis of the two-level games that develop at intergovernmental fora, and does so through an investigation of the 2020 negotiations that led to the institution of the Pandemic Crisis Support, first, and the The Next Generation EU, later on. Finally, it illustrates which alterations in the institutional design of the European Stability Mechanism could represent a different, and more favorable, structure of incentives for lenders and borrowers.